PENGEMBANGAN KOMPETENSI GURU MELALUI PELATIHAN PENGGUNAAN MIRO SEBAGAI MEDIA PEMBELAJARAN - Putri Anugrah Cahya Dewi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
In the ever-growing digital era, the integration of technology in education is becoming increasingly important. Education, which is now aimed at Generation Z and Alpha as the internet generation, needs to implement various technology-based learning innovations. Teachers as the main facilitators in the learning process must continue to improve their competence in the use of technology, including platform collaborative like Miro. Miro offers various features that can support interactive and collaborative learning, but there are still many teachers who do not have sufficient skills to use them. The features available in Miro have been designed to be used in learning. The use of Miro as a learning medium is aimed at creating more innovative and interactive learning. The teacher competency development method used is the training method. This training was attended by 30 teachers from various educational backgrounds. The training starts with the delivery of material, direct practice with assistance, and evaluation in the form of a question and answer session. From the training provided, it was found that the teacher already understood the techniques for using Miro in learning. This can be seen from the practical results and evaluation results in the form of questions and answers at the final training session.